"The key to this immense metallized landscape": Reading J. G. Ballard's Crash as an Ecological Structure of Feeling. Issue 1 (April 2018) - Hageman, Andrew
Abstract : This essay aims to expand the range of approaches to studying Crash, and perhaps Ballard's fiction more broadly, by exploring the eco-ideological forms and structures within this novel. Specifically, the essay reads Crash within a historical context of emerging ecological awareness and concern—an era that included the nearly concurrent publications of Arne Naess's theory of Deep Ecology, Lovelock and Margulis's Gaia Hypothesis, Raymond Williams's The Country and the City, and Gregory Bateson's Steps to an Ecology of Mind, to name a few key cultural influences. By attending to the landscapes, especially as they converge with infrastructure, and other nonhuman elements of Crash, this essay shifts the heretofore overwhelming critical focus on the human body in scholarship on this novel to an ecocritical focus on its narrative of systems and structures within which people live and evolve. Ultimately this essay claims that ecocritical study of novels like Crash provokes us to work through retrograde ideologies of Nature and what it means to be human as we can plan for our existence in the Anthropocene.